Analysis Of Regional Fixed Asset Management At The Regional Financial And Asset Management Agency In Medan - Putri Febrianti; Nurwani Nurwani; Nurlaila Nurlaila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to analyze the management of regional fixed assets at the Regional Finance and Asset Agency (BKAD) of Medan City. The type of research method used in this research is descriptive-qualitative. Data collection techniques used are interviews, observation, literature, and documentation. The subject of this research is the fixed asset manager. The results of this study indicate that regional asset management at the Medan City Regional Finance and Assets Agency (BKAD) has been carried out based on PERMENDAGRI guidelines No. 19 of 2016 regarding systems and procedures for managing Regional Property (BMD). The management of fixed assets at the Regional Finance and Assets Agency (BKAD) in Medan City can be stated as good, but the facilities and infrastructure are insufficient for the large number of employees in the office. In this case, many computers are unused or have been badly damaged, making them unfit for reuse.